Melanotic Schwannomas Are Rarely Seen Pigmented Tumors with Unpredictable Prognosis and Challenging Diagnosis - Elif Keskin; Sumeyye Ekmekci; Ozgur Oztekin; Gulden Diniz (Case Reports in Pathology)
Melanotic Schwannoma (MS) is rarely seen and potentially malignant neoplasm that is categorized as a variant of Schwannoma. MS most frequently involves intracranial structures followed by posterior nerve roots in the spinal canal. Approximately 50% of the cases with MS have psammomatous calcifications and this type of MS is related to Carney complex with autosomal dominant inheritance. Most cases of MS are benign, though 10% of them are malignant with metastatic potential. MS mimics melanoma and the differential diagnosis should be made excluding other melanin producing neoplasms especially melanoma. Case 1. A 42-year-old hypertensive male presented for checkup. He had a well-defined extraspinal oval lesion measuring 3.5 × 2.5 cm near right adrenal. Case 2. A 22-year-old female presented with neurofibromatosis-2, bilateral acoustic schwannomas and café au lait lesions on sacrococcygeal region. She had an intradural extramedullary lesion measuring 6.1 × 2.0 cm at L1-2 level. MS is a rare neoplasm composed of Schwann cells and melanin pigment. These tumors are usually benign but they may become aggressive. The biologic behavior of MS is difficult to predict; the patients have to be followed up for a longer period due to its malignant potential.